The Tao: Path of Simplicity and Humor (Journal of Parents and Teachers, 2025)
The article defines the TAO as a Chinese philosophy that refers to the concept of "the way" or "fundamental principle," which is the source and pattern of everything that exists in the universe. It is a central term in Taoism, a spiritual and philosophical tradition that emphasizes harmony with nature and the universe. Furthermore, it focuses on the natural path, duality, non-action, and literature.